Comparison of app-based and clinically administered matrix sentence tests in cochlear implant users - Kliesch, Sven; Brendel, Martina; Schulte, Michael; Lenarz, Thomas; Büchner, Andreas (Frontiers in Audiology and Otology, 2025)
ObjectiveTo evaluate the feasibility and reliability of a smartphone-based, self-administered matrix sentence test for assessing speech perception in cochlear implant (CI) users, and to compare its outcomes with those of the standard clinical Oldenburg Sentence Test (OLSA) in free-field conditions.MethodsNineteen adult CI users (12 experienced, 7 newly implanted) completed a standard open-set OLSA testing and a closed-set version using a research smartphone app with direct Bluetooth streaming to their hearing devices in a sound-treated room. The app presented five response alternatives per sentence and estimated speech reception thresholds (SRTs) at 60% word recognition to account for increased chance level. Test-retest differences and between-group effects were analyzed using mixed-model ANOVA and post hoc t-tests.ResultsAll participants were able to complete the smartphone-based test independently. SRTs obtained via the app showed strong agreement with clinical measures, particularly among experienced users. Larger deviations were observed in three newly implanted participants. The ANOVA revealed a significant effect of experience level (p = 0.02), but no effect of test method and no interaction. Usability was rated high, and the simplified five-option interface was well tolerated across age groups.ConclusionThe results demonstrate that smartphone-based matrix sentence testing with direct audio streaming is a feasible and reliable method for assessing speech-in-noise perception in CI users. This approach offers potential for remote monitoring and self-assessment beyond the clinical setting.